Pengaruh E-Service Quality Terhadap Kepuasan Pelanggan Halodoc dengan Trust Sebagai Mediasi - Yenchristie, Febby Angelina; Efendi (Jurnal Manajemen, 2025)
The research focuses on the impact of e-service quality on customer satisfaction of Halodoc with the mediation of trust. There are 6 variables – namely, user interface, responsiveness, need fulfillment, security, and customer service – which will be examined whether they have a direct effect on satisfaction and trust as mediation on customer satisfaction. This research involved respondents aged 17-50 years in Jakarta, Bogor, Depok, Tangerang, Bekasi. Data was collected online using Google Forms. The data were processed using SMART PLS to solve the 11 hypotheses of this study. The results of this study indicate that trust, user interface, and responsiveness do not have a direct effect on satisfaction. Meanwhile, need fulfillment and customer service have a direct influence on satisfaction. Trust as a mediator influences the effect of security on satisfaction, and customer service on satisfaction. Meanwhile, the user interface variables, responsiveness, and need fulfillment through trust mediation do not affect satisfaction.